2015
DOI: 10.1111/anu.12373
|View full text |Cite
|
Sign up to set email alerts
|

In vitroselection of a synbiotic andin vivoevaluation on intestinal microbiota, performance and physiological response of rainbow trout (Oncorhynchus mykiss) fingerlings

Abstract: The aim of this study was to determine the best synbiotic combination (based on growth and short chain fatty acids production) between Pediococcus acidilactici and five prebiotics in vitro, inulin, fructooligosaccharide (FOS), xylooligosaccharide (XOS), galactooligosaccharide (GOS), isomaltooligosaccharide (IMO). The best in vitro growth under aerobic and anaerobic culture condition was observed in the treatment, P. acidilactici + GOS. Furthermore, the study of short chain fatty acids (SCFA) production at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 42 publications
8
54
1
Order By: Relevance
“…The literature review revealed contradictory results regarding the effect of GOS on fish growth performance and feed efficiency. Though, there are some reports confirmed improvement of growth performance in GOS-fed red drum [12,16], Caspian roach fry [10], this prebiotic had no significant effects on performance of rainbow trout [35], Hybrid Striped Bass (Morone chrysops × Morone saxatilis) [13]. These differences can be attributed to species, life stage, dosage and experimental condition and highlighted the necessity of evaluation of different prebiotics on desired species.…”
Section: Discussionmentioning
confidence: 96%
“…The literature review revealed contradictory results regarding the effect of GOS on fish growth performance and feed efficiency. Though, there are some reports confirmed improvement of growth performance in GOS-fed red drum [12,16], Caspian roach fry [10], this prebiotic had no significant effects on performance of rainbow trout [35], Hybrid Striped Bass (Morone chrysops × Morone saxatilis) [13]. These differences can be attributed to species, life stage, dosage and experimental condition and highlighted the necessity of evaluation of different prebiotics on desired species.…”
Section: Discussionmentioning
confidence: 96%
“…(); Hoseinifar, Mirvaghefi et al. (). Lactobacillus plantarum 7–40 was first cultured in MRS broth for 24 hr at 37°C, then centrifuged at 3,000 × g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Synbiotics, a combination of prebiotics and probiotics, have been used since 2005 (Panigrahi et al., ). Synbiotics have been widely applied and are assumed to be growth‐ and immunity‐promoting factors in freshwater fish (Azimirad, Meshkini, Ahmadifard, & Hoseinifar, ; Hoseinifar, Dadar, & Ringø, ; Hoseinifar, Esteban, Cuesta, & Sun, ; Hoseinifar, Mirvaghefi, Amoozegar, Merrifield, & Ringø, ) and marine fish (Ai et al., ; Reyes‐Becerril et al., ). It is surprising that although growth‐enhancing effect of synbiotics on the growth of fish is well documented, little information was reported in cultured Penaeid shrimp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐digestible oligosaccharides such as FOS can be consumed as substrate by potentially beneficial microbial community and increase their number and dominance (Ringø et al, ) either by their presence or through fermentation and production of health‐promoting substance such as SCFAs (Hoseinifar, Sun, et al, ). From the few available works, the main valuable effects reported for those prebiotics in fish were improvements of growth performance, digestibility and immunity (Guerreiro, Serra, Oliva‐Teles, & Enes, ; Hoseinifar, Mirvaghefi, Amoozegar, Ringø, & Merrifield, ). However, few studies were available regarding prebiotics use in this species.…”
Section: Introductionmentioning
confidence: 99%